The flotation behavior and adsorption mechanisms of 2-((2-(decyloxy)ethyl)amino)lauric acid on quartz surface. (March 2018) - Luo, Binbin; Zhu, Yimin; Sun, Chuanyao; Li, Yanjun; Han, Yuexin
Highlights: A novel surfactant 2-((2-(decyloxy)ethyl)amino)lauric acid was synthesized firstly. Ether atom, imino and carboxyl polar groups improved the activity and solubility. Collecting recovery of the new collector LDEA on quartz reached above 98.0% at 15 °C. Different adsorptions on the quartz was studied, especially the hydrogen adsorption. Abstract: A novel surfactant 2-((2-(decyloxy)ethyl)amino)lauric acid (LDEA) – substituting 3-(decyloxy)propan-1-amine (DPA) on the α-carbon position of lauric acid was firstly synthesized and utilized as a collector for the flotation of quartz mineral at a relatively low temperature. The flotation performances and adsorption mechanisms of LDEA collector on quartz mineral surface were investigated by zeta potential measurements, Fourier transform infrared (FT-IR) spectroscopy, and X-ray photoelectron spectroscopy (XPS), in conjunction with the results of quartz micro-flotation tests. The flotation results showed that LDEA exhibited an excellent collecting performance on quartz mineral at a wide pulp pH range (about 6–11) with a low collector concentration 15.0 mg/L at a relatively low temperature 15 °C, where above 95.0% of the quartz mineral could be floated. Zeta potential measurements, FT-IR spectra, and XPS analyses reveal that the LDEA collector could be adsorbed on the surface of pure quartz in the forms of electrostatic and hydrogen bonding interactions at pulp pH 10.0.